Pengujian Dan Penjaminan Kualitas Software Point Of Sale Toko Elektronik Dengan Metode Black Box Funsional Dan Integrasi - Handono, Bagus Tri; Gunawan, G; Hartono, Rudi; Khotimah, Nur; Zy, Ahmad Turmudi (STIKOM Tunas Bangsa Pematangsiantar, 2024)
This Electronic Retail Point of Sale (POS) Software discusses testing and quality assurance methods for the POS application. This application is crucial in the context of managing sales and purchases in electronic stores. The goal of this documentation is to ensure that the application functions properly, meets user needs, and maintains the security of transaction data. The selected method for testing and quality assurance is the BlackBox method, with a particular focus on functional and integration testing. Functional testing includes steps such as opening the application, logging in with valid and invalid data, and testing the main features of the application. Meanwhile, integration testing focuses on the interaction between the key components of the application, such as master data, transaction data, and reporting. The importance of security in the POS application is emphasized through security testing, especially concerning logout mechanisms and post-logout access security. This is done to safeguard sensitive transaction data and customer information.